Distorted sound perception and subjective benefit after stapedotomy – a prospective single-centre study. (3rd June 2019) - Bächinger, David; Röösli, Christof; Kesterke, Rahel; Dalbert, Adrian; Péus, Dominik; Veraguth, Dorothe; Pfiffner, Flurin; Huber, Alexander
Abstract: Objective: To evaluate the quality of perceived sound after stapedotomy over a 1-year follow-up period focussing on incidence of dysacusis, particularly distorted sound perception (DSP). DSP was assessed by (i) determination of the frequencies and hearing level that such perceptions are elicited by pure tones (pure-tone-evoked distorted sound perception, PTE-DSP), a novel psychoacoustic measurement introduced in this paper, and (ii) assessment of patient-reported occurrence of DSP using the Amsterdam Post Operative Sound Evaluation (APOSE) questionnaire (APOSE-DSP). Design: Prospective study. Study sample: Patients ( n  = 23) with otosclerosis undergoing stapedotomy. Results: An air-bone gap of <20 dB was achieved in 100% of the patients. Three weeks postoperatively, 48% of the patients reported measured PTE-DSP and 39% of the patients experienced APOSE-DSP. The PTE-DSP significantly decreased during the 1-year follow-up period ( p  = 0.03). Postoperatively, APOSE-DSP was associated with a smaller benefit (improvement in air conduction; p  = 0.03), yet, a lower bone conduction pure-tone average was associated with PTE-DSP ( p  = 0.006). Conclusions: DSP after stapedotomy is associated with a smaller benefit 3 months after stapedotomy. DSP commonly occur after stapedotomy, but decrease over time. This is important information to be included in patient counselling before stapedotomy.